Transporting Pesticides and Understanding the Rules of the Road: Pest Control Businesses - Frederick M. Fishel (EDIS)
PI-161, an 8-page illustrated fact sheet by Frederick M. Fishel, addresses the concern for transporting pesticides that are regarded as hazardous materials by the Secretary of Transportation. This document is specifically written to provide information for those who are in the pest control service industry. Published by the UF Department of Agronomy, January 2008.